Bulgarians in Croatia : migrations, presence, identity - Grbić, Jadranka (Array, 2012)
The paper focuses on the members of the Bulgarian minority in Croatia. It analyses the reasons that have led a portion of the Bulgarian population to emigrate from their home country in the past, determining chronologically and defining different stages of the emigration, choices of migratory destinations and structural features of each stage. It describes the ways of settling in the migratory areas and the processes that turned these, initially seasonal migrations into permanent ones. A special attention was given to the migrations of the labour/professional group of vegetable growers. These were the migrators that accounted for (and this seems to apply to their descendants today) the majority of the total Bulgarian population in Croatia (according to the 2001 census, 327 citizens of Croatia declared themselves as Bulgarians). Furthermore, the migration of the vegetable growers is seen as part of a much wider, mass migration that occurred in Europe and beyond in the past - so wide and so specific that it earned them their own micro- ethnonym of a kind: Bulgarian gardeners.The consequences of migrations to immigrant locations have been analysed (outskirts of larger and major cities) from the economic, demographic and socio- cultural perspectives. In keeping with the recently popular migration and minority theories, the paper closes with the commentary on the present status of Bulgarians in Croatia as one of the twenty-two national minorities that have been recognized by the Croatian Constitution, and, finally, the factors that have influenced the creation of the identification strategies and practices of the members of this ethnic minority.